PEMBATASAN JUMLAH AKTA NOTARIS BERDASARKAN KEWAJARAN DI KOTA PADANG - Harris, Rionald; Daulay, Zainul; Benni, Beatrix (Universitas Ekasakti, 2019)
The Honorary Board of the Indonesian Notary Association as the organ of the Indonesian Notary Association issues a regulation regarding the Fairness of the Deed Making Certificate per Notary for 20 deeds per day. Based on pre-research, there are still many notaries who do not know about the regulation in Padang. Why a Notary is prohibited from making a deed exceeding the fairness limit, what factors becomes the reasons for a Notary in Padang to make a deed exceeding the fairness limit and the legal consequences of a deed exceeding the fairness limit will be the topic of discussion in this paper. The research method used is a type of empirical juridical research and the nature of analytical descriptive research; data collection is done by using data in the form of primary material as primary data, supported by secondary and tertiary materials. The data obtained are then processed, analyzed, and interpreted qualitatively. Compliance is a virtue that moves people to act rationally in using what is fair, it is important for Notary to be given reasonable limits on the deeds that they can make per day so that the Notary does not exceed their physical ability to make daily deeds. The Law of Notary Position does not limit the number of deeds that can be made by the Notary per day, so that there are still notaries who make the deed exceed the reasonable limits set especially Fiduciary deed in Padang. Notary Deed that exceeds the fairness limit determined by the Honorary Board of Notary will not be degraded to privately-made deed, provided that what is done by Notary in making the deed is in accordance with the Law of Notary Position. The reasonable limit of making a daily deed issued by the Indonesian Notary Association Honorary Board should be included in the Minister Law or Regulation because basically the DKP.INI 1 regulation in 2017 only binds members of the association. Had the notary been expelled from the association, it would not have had any effect on his position.